Clinical Profile of Patients with Temporomandibular Disorders Referred to a University Clinic. Issue 3 (2nd October 2015) - Maciel, Amanda Ramos Regis; Santana, Lucas Garcia; Gomes, Gabriel Dornellas; Orlando, Patrícia Ribeiro; Clemente, Thiago Victor; Oliveira, Evandro Silveira de; Douglas de Oliveira, Dhelfeson Willya; Anéas, Geruza Costa Gonzaga; Gonçalves, Patrícia Furtado; Flecha, Olga Dumont
Abstract: Aim: The aim of this study was to report a retrospective study on the profile of patients seen in the last 11 years [2004–2014], in a TMD clinic at the Federal University of the Jequitinhonha and Mucuri Valleys. Methods: All medical records were evaluated from January 2004 to December 2014. The following items of information were collected: gender, age, parafunctional habits, main complaints and treatment offered. The data collected were analyzed by using SPSS 22.0 software. Results: A total of 560 patient records related to 448 [80%] women and 112 [20%] men were evaluated. The age ranged from 10 to 93 years. Etiologic factors were reported in 374 [66.8%] records. There was an association between age and abuse [ p  = 0.003]. There was no significant association between treatment and gender [ p  = 0.361]. Conclusion: The profile of TMD patients seen in the last decade [2004–2014] was characterized by the majority being female patients, mean age 34.94 years and having some parafunctional habit.